2010
DOI: 10.1111/j.1365-2486.2009.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of climatic and crop varietal changes to crop production in the North China Plain, since 1980s

Abstract: The North China Plain (NCP) is the most important agricultural production area in China. Crop production in the NCP is sensitive to changes in both climate and management practices. While previous studies showed a negative impact of climatic change on crop yield since 1980s, the confounding effects of climatic and agronomic factors have not been separately investigated. This paper used 25 years of crop data from three locations (Nanyang, Zhengzhou and Luancheng) across the NCP, together with daily weather data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
196
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(216 citation statements)
references
References 26 publications
16
196
1
3
Order By: Relevance
“…This result was consistent with the finding in some other researches [7,17,18], which suggesting that temperature was above the optimal temperature of rice production and increasing temperature might reduce yield. However, T avg during RGS 2 and RGS 3 were significantly positively related to rice yield in some regions, which was consistent with other studies [12,19]. This result indicated that present T avg might be in the optimal temperature range and increasing temperature might increase yield.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This result was consistent with the finding in some other researches [7,17,18], which suggesting that temperature was above the optimal temperature of rice production and increasing temperature might reduce yield. However, T avg during RGS 2 and RGS 3 were significantly positively related to rice yield in some regions, which was consistent with other studies [12,19]. This result indicated that present T avg might be in the optimal temperature range and increasing temperature might increase yield.…”
Section: Discussionsupporting
confidence: 82%
“…However, Li et al [9] investigated the relationship between wheat yields and climate at different spatial scales of China, proposing that some unclear climate-yield relationships at a large scale would emerge if they were observed at a smaller scale. Some recent studies also pointed out that crop yields are not always negatively associated with an increased average temperature based on site observations in China [10][11][12]. Such observations are inherently inconclusive and dependent upon the selection of sites, thus making them difficult to represent a regional situation [7].…”
Section: David Publishingmentioning
confidence: 99%
“…To capture these drought stress effects in the plant and allow multi-year simulations, we chose to use a model with accurate representation of physiological responses to drought and a soil water balance that can be simulated continuously from one year to the other, also during fallows. The APSIM model (Keating et al, 2003) has been developed especially for semi-arid environments and has been extensively validated for wheat (Asseng et al, 1998a,b;Probert et al, 1998) and maize (Nelson et al, 1998), also in the North China Plain (Chen et al, 2010a,b;Liu et al, 2010). The model simulates crop growth and the soil water balance and can simulate a sequence of different crops with intermittent fallow periods.…”
Section: Apsim Calibration and Validationmentioning
confidence: 99%
“…A widely applied approach to estimating climate change impact on crop yield is crop simulation modeling (e.g., Lin et al, 2005;Liu et al, 2010;Tao et al, 2009;Xiong et al, 2012;Xiong et al, 2007;Zhang et al, 2013), where key socio-economic factors other than climate variables in crop production are typically out of consideration (Challinor et al, 2009). …”
Section: Introductionmentioning
confidence: 99%